2015
DOI: 10.1007/s10531-015-0979-4
|View full text |Cite
|
Sign up to set email alerts
|

Bryoflora of the Itatiaia National Park along an elevation gradient: diversity and conservation

Abstract: Bryoflora of the Itatiaia National Park along an elevational gradient: diversity and conservation). Itatiaia National Park harbors a unique bryoflora due to presence of different forest formations and well-defined climatic and vegetation bands: Montane Forest, Upper Montane Forest, and High-Altitude Fields (Campos de Altitude). Analysis of bryophyte diversity was undertaken to elucidate the richness and floristic composition of the different Atlantic Forest formations and to investigate the influence of elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
4
9
0
Order By: Relevance
“…The family Leucobryaceae was represented by 19 species (2 Brazilian endemics) in our study, and Costa et al (2015) also observed this in Rio de Janeiro state.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The family Leucobryaceae was represented by 19 species (2 Brazilian endemics) in our study, and Costa et al (2015) also observed this in Rio de Janeiro state.…”
Section: Discussionsupporting
confidence: 87%
“…These authors indicated that bryophtes were the richest and most diverse above this elevation. The results of several other authors are consistent with this finding , Frahm 1990, Gradstein 1991, Kessler 2000, Santos and Costa 2010, Costa et al 2015.…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations